2017
DOI: 10.1136/bmjgh-2016-000212
|View full text |Cite
|
Sign up to set email alerts
|

Measuring, manipulating and exploiting behaviours of adult mosquitoes to optimise malaria vector control impact

Abstract: Residual malaria transmission can persist despite high coverage with effective long-lasting insecticidal nets (LLINs) and/or indoor residual spraying (IRS), because many vector mosquitoes evade them by feeding on animals, feeding outdoors, resting outdoors or rapidly exiting from houses after entering them. However, many of these behaviours that render vectors resilient to control with IRS and LLINs also make them vulnerable to some emerging new alternative interventions. Furthermore, vector control measures t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
86
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(93 citation statements)
references
References 67 publications
(101 reference statements)
5
86
2
Order By: Relevance
“…It is also telling that a similar, and perhaps more surprising, the pattern was observed for the notoriously anthropophagic [6,27,49,50] An. gambiae when compared with a previous study of the same species in a rural Tanzanian context (Figure 3).…”
Section: Position Of Figuresupporting
confidence: 59%
See 2 more Smart Citations
“…It is also telling that a similar, and perhaps more surprising, the pattern was observed for the notoriously anthropophagic [6,27,49,50] An. gambiae when compared with a previous study of the same species in a rural Tanzanian context (Figure 3).…”
Section: Position Of Figuresupporting
confidence: 59%
“…This newly observed behavioural plasticity, allows the mosquito to evade human-targeted insecticidal based interventions by allowing it to access safer alternative blood sources [29,30]. This behaviour may help vector species to sustain its population and contribution to residual malaria transmission by evading fatal contact with existing front-line interventions [6,31,32].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed a promising array of new vector control products and prototypes, such as attractive sugar baits, vapour-phase insecticide emanators, veterinary insecticides and house entry traps, are now emerging that could be horizontally delivered to end users almost anywhere in some of the poorest countries in the world 20. Furthermore, all the adult mosquito behaviours which these intervention options target can be readily quantified with existing, accessible, well-established entomological field techniques 53. Such metrics of targetable mosquito behaviours may therefore be used to rationally select, monitor and evaluate optimal intervention choices, to maximise impact on malaria transmission 53…”
Section: Introductionmentioning
confidence: 99%
“…Malaria-transmitting mosquitoes are often described as primary or secondary vectors with this categorisation informed, in part, by their level of anthropophagy as indicated by their HBI. Owing to the influences of different environmental settings, however, studies reporting HBI for the same vector species demonstrate considerable variability 21,[23][24][25] . We recently showed that the HBI of Anopheles coluzzii varied significantly over an extraordinarily small spatial scale, thus demonstrating how localised host biting behaviour can be 26 .…”
mentioning
confidence: 99%